2001
DOI: 10.1182/blood.v97.6.1525
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 restores immunity in athymic T-cell–depleted hosts

Abstract: Thymic-deficient hosts rely primarily on antigen-driven expansion to restore the peripheral T-cell compartment following T-cell depletion (TCD). The degree to which this thymic-independent pathway can restore immune competence remains poorly understood but has important implications for a number of clinical conditions including stem cell transplantation and human immunodeficiency virus (HIV) infection. A model of HY-mediated skin graft rejection by athymic, TCD mice was used to show that restoration of naive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
95
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(99 citation statements)
references
References 60 publications
(24 reference statements)
3
95
1
Order By: Relevance
“…Also, T cell homeostasis is mediated by signals transmitted by growth factor receptors in secondary lymphoid and in nonlymphoid organs (3,49,53,54). IL-7 potently enhances thymic-independent peripheral expansion and restores immunity in athymic T cell-depleted hosts (55). Furthermore, IL-7 is required for homeostatic expansion of naive CD8 ϩ and CD4 ϩ T cells in lymphopenic hosts and is partially required for the homeostatic proliferation of memory cells (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, T cell homeostasis is mediated by signals transmitted by growth factor receptors in secondary lymphoid and in nonlymphoid organs (3,49,53,54). IL-7 potently enhances thymic-independent peripheral expansion and restores immunity in athymic T cell-depleted hosts (55). Furthermore, IL-7 is required for homeostatic expansion of naive CD8 ϩ and CD4 ϩ T cells in lymphopenic hosts and is partially required for the homeostatic proliferation of memory cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-7 is required for homeostatic expansion of naive CD8 ϩ and CD4 ϩ T cells in lymphopenic hosts and is partially required for the homeostatic proliferation of memory cells (22). These two studies point to IL-7 as an important cytokine in T cell homeostasis (22,55). Therefore, improved IL-7R␣ signaling by glucocorticoids may contribute to IL-7-mediated expansion of memory T cells and maintenance of the peripheral T cell repertoire (56 -58).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IL-7 availability is increased during primary HIV-1 infection and persists, likely as a response to or as a cause of lymphopenia. Indeed, IL-7 levels are inversely correlated with CD4 ϩ T cell counts (33)(34)(35)(36).…”
Section: H Uman Immunodeficiency Virus Infection Of Humans Ifmentioning
confidence: 99%
“…However, given the degree to which thymic function may be limited in clinical situations associated with T cell depletion, an important question is the extent to which the ability for IL-7 to enhance peripheral expansion can restore immune competence. Indeed, in a murine model assessing responses to a stringent antigen following T cell depletion of athymic mice, we have demonstrated that the administration of IL-7 can potently modulate functional immune responses (22). Thus, even in the complete absence of thymic function, potent effects of IL-7 in the periphery can lead to functional immune competence, thus improving the function of an otherwise limited repertoire.…”
mentioning
confidence: 99%
“…One clear effect of IL-7 on mature peripheral T cells is the inhibition of programmed cell death, which is present at high levels in patients with T cell depletion (22)(23)(24). IL-FRY AND MACKALL 804 FIG.…”
mentioning
confidence: 99%